Effect of Sports Participation on Subjective Well-Being: Instrumental Variable Results from Microdata - Liang, Chyi; Wu, Pei-Ling; Jane, Wen-Jhan (Asian Journal of Applied Economics, 2024)
Policymakers worldwide have increasingly recognized the importance of sports participation, believing it enhances people’s quality of life, overall social welfare, and life satisfaction. This study utilizes individual-level data from Taiwan’s “Exercise Current Situation Survey” in 2019 to investigate the impact of sports participation on subjective well-being. We propose an individual’s perceptions of the government’s promotion of sports and the adequacy of sports facilities as instrumental variables (IVs), and a two-stage Poisson regression (2sPR) model is employed for analysis. The results indicate that sports participation has a significantly positive effect on personal subjective well-being. Regressions by gender revealed that men derive more well-being from sports participation than women do. Body mass index (BMI) and years of schooling have a positive and significant influence on subjective well-being. Conversely, respondents’ age, urbanization, and health status exhibit significant negative effects.